Model Pembiayaan BMT BAHTERA: Studi Literatur tentang Praktik Inovasi Pembiayaan Mikro berbasis Syariah - Najmuddin, M.; Nurmulia, Rahmi; Rohmah, Wulan Lailatur; Asytuti, Rinda (Glossary : Jurnal Ekonomi Syariah, 2025)
Innovations in Islamic microfinance products at BMT BAHTERA play an important role in the development of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. This research analyzes various sharia-based financing product innovations at BMT BAHTERA, such as mudharabah, musyarakah and rahn, which have helped expand access to financing, increase financial inclusion, and encourage the growth of MSMEs. Using a qualitative approach through literature review and in-depth interviews, this research identifies that BMT BAHTERA's financing product development includes innovative features such as flexible payment schemes, customer mentoring and digital integration. Despite facing challenges such as limited understanding of MSMEs and the need for policy alignment, the potential for this product development is huge, supported by technological developments and increasing public awareness of Islamic finance. This research contributes to the Islamic finance literature and provides recommendations for further development to support the sustainable growth of MSMEs.